Lenguas artificiales y universos femeninos - Carmen Galán Rodríguez (Cuadernos LIRICO)
Artificial languages created by women have hardly been relevant to the masculine writing of linguistic ideas. Like so many other productions, they have been relegated to the nebulous space of the psychotic. This work seeks to claim the capacity of some of these authors to incorporate in new codes the expressive possibilities of language. In an extraordinary exercise of creative will, they create their own space of enunciation, perhaps the only truly free, within which their voice is legitimized.